2015
DOI: 10.1002/rsa.20601
|View full text |Cite
|
Sign up to set email alerts
|

Structure of random 312‐avoiding permutations

Abstract: We evaluate the probabilities of various events under the uniform distribution on the set of 312-avoiding permutations of 1, . . . , N . We derive exact formulas for the probability that the i th element of a random permutation is a specific value less than i, and for joint probabilities of two such events. In addition, we obtain asymptotic approximations to these probabilities for large N when the elements are not close to the boundaries or to each other. We also evaluate the probability that the graph of a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…Complementing this result, Proposition 4.2 shows that the number of points well below the diagonal is o(N) with high probability. Madras and Pehlivan [16] consider the properties of random 312-avoiding permutations below the diagonal in more detail. Theorem 1.2 also follows directly from recent independent work of Miner and Pak [19], who investigate fine asymptotics of P τ N (π i = j) for τ ∈ S 3 .…”
Section: Conjecture 11 (Ratio Limit Conjecture)mentioning
confidence: 99%
See 1 more Smart Citation
“…Complementing this result, Proposition 4.2 shows that the number of points well below the diagonal is o(N) with high probability. Madras and Pehlivan [16] consider the properties of random 312-avoiding permutations below the diagonal in more detail. Theorem 1.2 also follows directly from recent independent work of Miner and Pak [19], who investigate fine asymptotics of P τ N (π i = j) for τ ∈ S 3 .…”
Section: Conjecture 11 (Ratio Limit Conjecture)mentioning
confidence: 99%
“…In fact, they showed that L(4231) 9.47 while (k − 1) 2 = 9 for k = 4. For several years, the best published upper bound for L(4231) was 288 [7], until Claesson, Jelínek and Steingrímsson [11] recently proved that L(4231) 16; a more recent preprint of Bóna [9] lowers the upper bound to 7 + 4 √ 3 ≈ 13.93. So it remains an active open problem to find the exact value or an accurate estimate of L(4231).…”
Section: Introductionmentioning
confidence: 96%
“…For densities in the interior of double-struckF we study the shape of a typical permutation with those densities, again in the large n limit. We note that the typical shape of pattern‐avoiding permutations (which necessarily lie on the boundary of the feasible region double-struckF) has also recently been investigated .…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we consider the densities of one or more patterns and consider the feasible region, or phase space F, of possible values of densities of the chosen patterns for permutations in S n in the limit of large n. For densities in the interior of F we study the shape of a typical permutation with those densities, again in the large n limit. We note that the typical shape of pattern-avoiding permutations (which necessarily lie on the boundary of the feasible region F) has also recently been investigated [1,10,15,[26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…There is also a number of papers studying other properties of random -avoiding permutations. Some examples, in addition to those mentioned above, are consecutive patterns [6]; descents and the major index [5]; number of fixed points [21,22,25,26,39,44]; position of fixed points [25,26,39]; exceedances [21,22]; longest increasing subsequence [19]; shape and distribution of individual values i [24,37,38].…”
Section: Introductionmentioning
confidence: 99%